Approximation of Analytic Functions by Kummer Functions - Soon-Mo Jung (Journal of Inequalities and Applications, 2010)
We solve the inhomogeneous Kummer differential equation of the form xy′′+(β-x)y′-αy=∑m=0∞amxm and apply this result to the proof of a local Hyers-Ulam stability of the Kummer differential equation in a special class of analytic functions.